Properties of Clay as a Construction Material for Building Walls - Houda Ghailane, Mohamad Asmidzam Ahamat, and Ahmad Naim Ahmad Yahaya (International Journal of Advanced Science and Technology, 2020)
Clay plays a big role in construction industries and especially in the construction of building’s wall. The objective of this research work is to study the properties of clays that are suitable as construction materials to ensure high energy efficient buildings. Before any test was conducted, the clay sample was dried at 105±5°C for 18 hours. The particle size distribution was determined by measuring the mass of residual in sieves with various diameters (between 45 micrometer and 4 mm). For the particles with the size less than 2mm, the particle size distribution density was measured using laser-based particle size analyzer Sympatec GmbH GRADIS/L. After grinding the dry clay sample, its chemical elements determined using the Energy Dispersive X-ray Fluorescence Spectrometer Thermo Scientific QUANT’X EDXRF Analyzer. Rheology tests were conducted for the clay-water mixture, with the percentage of clay between 20% and 73%, using Anton Paar MCR 302 rheometer. It was found that the clay-water mixture follows shear thinning properties. The purpose of this study is to understand the behavior of clay used as construction material and enable the prediction of the appropriate amount of water to be added to clay which is used for the fabrication of fired bricks. The outcome of this study provides basis for better understanding of the clay’s properties. This information is fundamental for the fabrication process of fired clay bricks with enhanced physical, thermal, and mechanical properties, which will guarantee the energy efficiency of buildings.